Eating disorders in alcohol and non-alcoholic drug dependent women: a controlled study - Maner, Fulya; Erkıran, Murat; Hantaş, Yüksel (Journal of Dependence, 2004)
Objective: The comorbidity of eating disorders (ED) with other psychiatric disorders is of special interest in recent years. In this study we investigated 56 females who met DSM-IV criteria for alcohol or drug use disorders. Method: We conducted the study in Bakırköy State Hospital of Training and Research for Psychiatric and Neurological Diseases, between October 2001 and February 2002. The control group consisted of 41 females within the same age range who had no history of drug use disorder. The sociodemographic and clinical features of the two groups were assessed with a semi-structured form which was developed for the purpose of the study. We applied Eating Attitudes Test and DSM-IV eating disorders questionnaire list. Results: Being divorced in alcohol/drug dependent group and being married in control group were found statistically significantly higher. Rate of eating disorder in alcohol/ drug dependent group (%16.1) was statistically significantly higher than control group (%2.4). Three (%33.3) of the 9 eating disorder patients were bulimic and 6 (%66.6) of them were atypical ED. Conclusion: Our results showed the importance of the questioning eating disorder among alcohol or drug dependents.